Sustaining U.S. Nuclear Submarine Design Capabilities - Schank, John F. (RAND Corporation, 2007)
Nuclear submarine design resources at the shipyards, their suppliers, and the Navy may erode for lack of demand. Analysis of alternative workforce and workload management options suggests that the U.S. Navy should stretch out the design of the next submarine class and start it early or sustain design resources above the current demand, so that the next class may be designed on time, on budget, and with low risk.